2017
DOI: 10.17261/pressacademia.2017.680
|View full text |Cite
|
Sign up to set email alerts
|

The role of individual factors on online shopping behavior

Abstract: Based on the rapid growth of e-commerce and online shopping, this study explores behavioral intention of consumers of online shopping websites. Methodology: Consumer's individual factors' effect on consumer perceived usefulness of online shopping and user satisfaction are modelled and examined in terms of effects on behavioral and purchase intention toward online shopping websites. Data were collected via Internet survey and 318 usable surveys of consumers were gathered. Findings: The results suggest that cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
(99 reference statements)
0
1
1
Order By: Relevance
“…The study also has some practical implications. First, although previous studies found that perceived benefits motivate potential participation in value co-creation (McElroy et al, 2007;Alan et al, 2017), the findings of this study imply that HEIs should pay more attention to fostering and engaging individuals with knowledge self-efficacy and commitment as they are very significant stimuli for engaging in value cocreation. This can be implemented via workshop training, seminars, and gatherings within the HEI community designed to encourage individuals to practice affective commitment and gain knowledge self-efficacy through continual participation in value co-creation activities.…”
Section: Theoretical and Practical Implicationscontrasting
confidence: 59%
See 1 more Smart Citation
“…The study also has some practical implications. First, although previous studies found that perceived benefits motivate potential participation in value co-creation (McElroy et al, 2007;Alan et al, 2017), the findings of this study imply that HEIs should pay more attention to fostering and engaging individuals with knowledge self-efficacy and commitment as they are very significant stimuli for engaging in value cocreation. This can be implemented via workshop training, seminars, and gatherings within the HEI community designed to encourage individuals to practice affective commitment and gain knowledge self-efficacy through continual participation in value co-creation activities.…”
Section: Theoretical and Practical Implicationscontrasting
confidence: 59%
“…These studies have mostly focused on the customers' perceived benefits as the main factor motivating customer online engagement behavior in value co-creation. However, few studies have investigated customer personal factors and their impact on customer online behavior (McElroy et al, 2007;Alan et al, 2017). To this end, the aim of this study is to empirically examine customer-personal factors that lead to value co-creation engagement, considering HEI technological capabilities that guarantee such useful interactions occur.…”
Section: Introductionmentioning
confidence: 99%